2022
DOI: 10.1080/18366503.2022.2025687
|View full text |Cite
|
Sign up to set email alerts
|

An extended human reliability analysing under fuzzy logic environment for ship navigation

Abstract: Q2 :The disclosure statement has been inserted. Please correct if this is inaccurate.Response: Yes, it is correct. Q3 :The reference "Castiglia and Giardina 2013" is listed in the references list but is not cited in the text. Please either cite the reference or remove it from the references list.Response: Please remove it. Q4 :The reference "Erdem et al. 2021" is listed in the references list but is not cited in the text. Please either cite the reference or remove it from the references list. Response: It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Expert opinions are particularly valuable in scenarios with high environmental uncertainties and challenges in collecting historical data [26,27]. These opinions are processed using fuzzy set theory to assess BEs using linguistic terms, thereby translating them into quantifiable fuzzy membership values essential for subsequent FTA [28].…”
Section: Calculation Of Polar Environment-induced Failure Probability...mentioning
confidence: 99%
“…Expert opinions are particularly valuable in scenarios with high environmental uncertainties and challenges in collecting historical data [26,27]. These opinions are processed using fuzzy set theory to assess BEs using linguistic terms, thereby translating them into quantifiable fuzzy membership values essential for subsequent FTA [28].…”
Section: Calculation Of Polar Environment-induced Failure Probability...mentioning
confidence: 99%
“…32 Uflaz et al and IlkeSezer et al utilized HRA for the assessment of ship managers. 33,34 Zare et al investigated human reliability in the petrochemical industry. They employed the Analytic Hierarchy Process (AHP) to assign weights and rank the Performance Shaping Factors (PSFs) and human errors.…”
Section: No No Nomentioning
confidence: 99%
“…Based on Equation ( 22) through Equation ( 32), and by simplifying the expressions and identifying constant parameters, the HEP be represented as Equation (33). In this study, the primary objective is to minimize the HEP, which is equivalent to enhancing workforce reliability.…”
Section: 𝑇𝐶 𝑅mentioning
confidence: 99%
“…The results revealed that safety culture, fatigue, time limitation, and experience are deeply influential on crew performance (Erdem & Akyuz, 2021). Uflaz et al (2022) outlines the principles of fuzzy-based shipboard operation human reliability analysis (SOHRA), which is used to quantitatively assess human error during ship preparation procedures for navigation. The overall human error probability for preparing the ship for sailing is found to be 1.49E-01.…”
Section: Introductionmentioning
confidence: 99%
“…The overall human error probability for preparing the ship for sailing is found to be 1.49E-01. It is stated that the study will provide practical contributions to shore-based safety professionals, ship managers and masters of the ship (Uflaz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%